Análisis de los procesos comunicacionales que genera Liga Deportiva Cantonal de Macará y su incidencia en los medios de comunicación local y comunidad en general, período septiembre 2012 – febrero 2013. Propuesta alternativa - Gualan Vega, Luis David (2014)
The sport or physical activity performed as competition is taken into consideration today as a fundamental part of the development, growth and education of children, youth or adults whose practice allows the entities involved to stay away from negative aspects such as alcohol, drugs and even a sedentary lifestyle. Enabling young athletes as part of Liga Deportiva Cantonal Macará, future generations and the community in general, sports information for guidance, learn and enjoy the alternatives of physical activity, will be useful for all, because that will be more active and dynamic society. In Macará media as Maxivisión, Macará TV and 99.7 FM Stereo Macará not allocated a certain space for the fan, neighborhood or school sport, highlighting athletes Liga Deportiva Cantonal, and the disciplines that comprise because the information generated is lost due to lack of space or means of dissemination. This motivated to perform this research called ANALYSIS PROCESS GENERATING COMMUNICATIONAL CANTONAL SPORTS LEAGUE OF MACARÁ AND ITS IMPACT ON LOCAL MEDIA COMMUNICATION AND COMMUNITY IN GENERAL, PERIOD SEPTEMBER 2012 –FEBRUARY 2013. Alternative proposal as research subjects taking the young men and women athletes who are part of Cantonal League, managers, coaches, and former directors of the institution, and outreach workers of those interesting conclusions and recommendations were obtained. It should be noted that the research is justified as a matter of interest and social situation, also because Macará has been having success in inter-cantonal sports games made in the different cantons of the province of Loja, Macará also is preparing to host intercantonal XI 2014 games. During the investigation as scientific methods, including observation and research techniques, including inquiry, which allowed direct attention to the problem was used; the survey was administered to a total of 377 people, distributed among athletes Liga Deportiva Cantonal Macará, managers, coaches, journalists, teachers, officials, parents, athletes, and citizens in general, and the interview was directed to Liga Deportiva Cantonal President Macará, Mr. Luis Paucar. With the results of the survey applied we emphasize that most citizens claimed to be the president of the institution which is responsible for disseminating information to the media, however argues that Liga not adequately informs its functions as the name of the institution is appointed only when participating in sporting events, mentioning that there is a considerable neglect. Athletes like their parents agree on the lack of promotion of young people in the media, also stating that their activities are not known to all the people. Meanwhile sports leaders and coaches say they are convinced that LDCM not properly report your activities you do, that communication is internal, but should compartírsela with the public through the media since it is not the athlete is touted as such. The same criterion of journalists and media stating that LDCM not adequately informs its activities and promotes its athletes, arguing that perhaps the lack of budget, lack of knowledge in the field of communication or by carelessness or neglect their directory. With this information the conclusions, among which stand to Liga Deportiva Cantonal de Macará not adequately informs the community activities, mainly by promoting athletes there are formed, being at odds most of the public respondents were drawn; Citizenship also known positioning Liga Deportiva Cantonal having determined that the activities and qualities of the athlete are not promoted entirely by the local media. So then between the tips it is determined that: It is suggested to the institution that agreements take the directory, the information generated, and the process of working with athletes, is informed by the media so that citizens have a track sporting events in the canton Macará; as the importance of asking the media the possibility of creating a sports space, which contains local information, especially for the benefit of the training of athletes, allowing the public to discuss and learn about the work being consistent athletes. So the proposal was directed to implement a television sports program, which is transmitted by Maxivisión Canal and can be relayed to the community of the rural sector through Macará Stereo 99.7 FM radio station, a place where sport is encouraged, because they allow full disclosure of athletic endeavor in all disciplines of Liga Deportiva Cantonal as well as amateur, neighborhood or school sports Macará canton.